Snippets of Courtly Love: Three Illuminated Manuscripts of the Metamorphoses from the 14th Century - Otero Moreira, Brianda (Eikón / Imago, 2024)
The main purpose of this contribution is to present three illuminated manuscripts of Ovid’s Metamorphoses, two preserved in the National Library of Spain (BNE) and one in the Sächsische Landesbibliothek – Staats- und Universitätsbibliothek Dresden (SLUB). The illuminations of the three codices present an apparent lack of correspondence with the mythological content of the text and have so far not been considered in studies of the illuminated Metamorphoses. Their analysis makes it possible to establish a clear relationship between the three manuscripts, as well as to delve more deeply into the outlook of the miniature of the Ovidian poem during the last centuries of the Middle Ages.